Setting research priorities to improve the health of children and young people with neurodisability: a British Academy of Childhood Disability-James Lind Alliance Research Priority Setting Partnership. Issue 1 (28th January 2015) - Morris, Christopher; Simkiss, Doug; Busk, Mary; Morris, Maureen; Allard, Amanda; Denness, Jacob; Janssens, Astrid; Stimson, Anna; Coghill, Joanna; Robinson, Kelly; Fenton, Mark; Cowan, Katherine
Abstract : Objectives: To engage young people, parent carers and clinicians in a systematic process to identify and prioritise research questions regarding ways to improve the health and well-being of children and young people with neurodisability. Design: British Academy of Childhood Disability (BACD)-James Lind Alliance research priority setting partnership bringing together patients, carers and clinicians as equal stakeholders. Setting: UK health service and community. Methods: The BACD Strategic Research Group formed the partnership. A Steering Group was established; charity and professional partner organisations were recruited. Suggestions were gathered in an open survey and from research recommendations for statutory guidance. Items were aggregated to formulate indicative research questions and verified as uncertainties from research evidence. An interim survey was used to rank the questions to shortlist topics. A mixed group of stakeholders discussed the top 25 questions at the final priority setting workshop agreeing a final rank order and the top 10 research priorities. Participants: Partner organisations were 13 charities and 8 professional societies. 369 people submitted suggestions (40% non-clinicians). 76 people participated in the interim prioritisation (26 parents, 1 young person, 10 charity representatives, 39 clinicians); 22 took part in the final workshop (3 young people, 7 parents, 3 charity representatives, 9 professionals). Results: The top three research priorities related to (1) establishing the optimal frequency and intensity (dose) for mainstream therapies, (2) means for selecting and encouraging use of communication strategies and (3) ways to improve children's attitudes towards disability. The top 10 included evaluating interventions to promote mobility, self-efficacy, mental health, continence, physical fitness, educational inclusion and reduce impacts of sleep disturbance. Conclusions: The methodology provided a systematic and transparent process to identify research priorities that included stakeholders that have typically not contributed to setting the research agenda. The top 10 and other topics identified provide a resource for researchers and agencies that fund research